The Experience of a Virtual Campus: Evaluation of Psychology Students´ Use of Internet - Ahumada Figueroa, Luis (Revista de Psicología, 2004)
This paper discusses the integration of a virtual learning procedure into a Social Psychology course. This resource is available through the Virtual Campus at the Pontificia Universidad Católica de Valparaíso, Chile (www.ucv-cv.cl). The site, designed for second year psychology students enrolled in the course, included topics not covered in the regular course and a methodology that fosters the development of a learning community. Content and methods were sought to integrate various disciplinary perspectives addressing psychosocial problems. More specifically, the virtual classroom complemented regular classroom instruction by providing a number of communication resources such as: discussion forums, opinion polls of controversial topics covered in class, and a chat room. Additionally, it included support texts, electronic materials, as well as instructions to search psychology-related databasis (i.e., PsychFirst, PsychINFO, and Econlit). Through a survey designed to assess the students’ use of Internet, pre (at the beginning of the academic year) and post (at the end of the year-long course) measures were obtained to examine the impact of this virtual learning procedure. Results show that students searched for information not covered in class and there was a significant change in the results assessed on the use of Internet as a learning procedure. The use of a teaching-learning methodology that includes a virtual tool improves the quality of teaching, by developing life long learning skills related to information management and knowledge of information and communication technologies (TICs).